Analisis Kinerja Berbasis Balanced Scorecard pada KSP TEB Artha Mulia yang Menerapkan Financial Technology - Pratiwi, Komang Desi Adi; Putra, I Nyoman Wijana Asmara (E-Jurnal Akuntansi; Vol 27 No 3 (2019)DO - 10.24843/EJA.2019.v27.i03.p11, 2019)
This study aims to determine and analyze the performance of cooperativ that has implemented financial technology, KSP TEB Artha Mulia, by using balanced scorecard. The sample is determined by the probability sampling for customers and non-probability sampling for employees. The results of the study show that the performance from financial perspective seen from the liquidity ratio and the capital adequacy ratio has reached the ideal standards and the profitability ratio has not reached the ideal standards. The performance of the customer perspective and the internal business process perspective show good results. The performance of learning and growth perspectives seen from the level of employee satisfaction and the level of employee productivity is good, but the employee retention rate shows results that have not been classified as good. This research is expected to be used as a reference for cooperatives to plan the right strategy in the future. Keywords : Performance; balanced scorecard; financial technology